Between the Risk of the Banking Sector and Macroeconomy on the Basis of Selected European Countries - Wyrwał , Julita (Studia Oeconomica Posnaniensia, 2018)
This paper presents the results of a study on the relationship between the risk of the banking sector and the macroeconomic condition of a given country. The measures of banking sector risk are bank indices. The study uses data from economically diverse European countries: stable and well-developed economies of Northern Europe such as Norway (2001-2017) and Sweden (2000-2017), Central- European Poland (1996-2017) and the unstable economies of Spain (2001-2017) and Italy (2009-2017). Models describing volatility are GARCH and Spline-GARCH. The realized variance was also used as a measure of volatility.